2017
DOI: 10.3311/ppci.10419
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Behaviour Factor of Medium Ductile SMRF Structures

Abstract: In seismic codes, the capacity of structures is calculated using capacity design procedure based on the concept of base shear. The critical parameter in this procedure is the behaviour factor (q-factor), which allows designing the structures at the ultimate limit state accounting for their ductility and reserve strength. In this paper, the q-factor is evaluated for medium ductile steel moment-resisting frames (SMRF) using pushover analysis. The influence of specific parameters, such as the stories number, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The corrected R value with respect to the earthquake series was found to have a lower value compared to the designed R (Abdollahzadeh and Sadeghi 2018). In a study, the effects of story height and column/ beam capacity ratio on behavior factor (q) were calculated for steel special moment resisting frames, with the results showing the q factor suggested by Eurocode-8 to be underestimated for low-rise structures (Yahmi et al, 2018). A study was conducted to find the effect of pf bracing system arrangement on R factor by performing non-linear pushover analysis, with the arrangement of bracing/shear walls at alternate bays showing an increased R factor (Tamboli and Amin, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The corrected R value with respect to the earthquake series was found to have a lower value compared to the designed R (Abdollahzadeh and Sadeghi 2018). In a study, the effects of story height and column/ beam capacity ratio on behavior factor (q) were calculated for steel special moment resisting frames, with the results showing the q factor suggested by Eurocode-8 to be underestimated for low-rise structures (Yahmi et al, 2018). A study was conducted to find the effect of pf bracing system arrangement on R factor by performing non-linear pushover analysis, with the arrangement of bracing/shear walls at alternate bays showing an increased R factor (Tamboli and Amin, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The revised response reduction factor (R) value with regard to the earthquake series was discovered [5]. The conclusion shows that the adjusted R is less than the intended R. In a study by Djamal Yahmi et al [6] to determine the impact of storey height and column/beam capacity ratio on behaviour factor (q) for steel special moment resistant frame (SMRF), it was discovered that the low-rise construction q factor recommended by Eurocode-8 is too low. By using non-linear pushover analysis, Kruti Tamboli and Amin.…”
Section: Introductionmentioning
confidence: 99%
“…According to Indian Standards [4], the reported R factor is remarkably higher than the actual scenario. Regarding the earthquake series, an updated R factor value was proposed [5], and the analysis findings demonstrated that the adjusted R is lower than the desired R. The behaviour factor (q), which is the European factor equivalent to R in Indian Standards, for steel special moment resisting frames (SMRF) proposed by Eurocode 8 for low-rise buildings, was found to be inadequate to ascertain the effects of the storey height and of the column to beam capacity ratios [6]. Tamboli and Amin [7] performed a non-linear pushover analysis to determine how the bracing system configuration may affect the R factor, finding that the latter increased by placing bracing/shear walls in different bays.…”
Section: Introductionmentioning
confidence: 99%